Potensi Desa Pagedangan Kecanatan Tukdana Indramayu dan Urgensi Penanganan Bullying pada Anak Usia Sekolah Dasar - Zamzami, Zamzami (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2024)
Pagedangan Village in Indramayu Regency, West Java, possesses significant natural and socio-cultural capital, including fertile agricultural land and strong community solidarity, offering a promising foundation for community development initiatives like the Community Service Program (KKN). However, this potential is threatened by social challenges, notably the pressing issue of bullying among elementary school children. This abstract highlights the existing potential of Pagedangan Village while underscoring the critical urgency of addressing bullying. Bullying can have severe and long-lasting negative impacts on the psychological and social development of children, hindering their well-being and future potential. Recognizing the detrimental effects on victims, perpetrators, and witnesses, a focused intervention is essential to create a safe and supportive environment for learning and growth. Leveraging the village's inherent strengths through collaborative efforts involving students, educators, parents, and community leaders is crucial for developing effective strategies to prevent and address bullying, thereby ensuring the holistic development of Pagedangan's young generation and maximizing its inherent potential.